PEMANFAATAN LIMBAH KULIT lKAN MENJADI KERUPUK (RAMBAK) - Kristianingrum, Susila; Arianingrum, Retno; Sulastri, Siti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2006)
This   program   of  implementation    Science,   Technology    and  Arts (Ipteks)  intended  to  introduce  and  give  skill  training  about  making  chips from  fish skins (kerupuk  kulit  ikan)  to the community   in Tanjungsari   Sub district,  Gunungkidul   Regency.  In this  area,  there  are  plenty  of  fish  skins that can pollute  and disturb  the beauty  of the environment.   Producing  chips from fish skins can reduce the pollutant  and increase  the value of fish skins.The  program   was  held  by  giving   information   and  demonstration methods  in two locations  with different  participants.   The first program  was held  in Tanjungsari  Sub-district   Hall  for 35 participants,   who  were  village chiefs'    wives.   The   second   program   was   held   at  Baron   beach   hall   to accommodate  20 participants,  consisting  of fishermen's   wives and members of youth group.The questionnaire  result  of first program  showed  that  85.71 % of theparticipants   considered  this  program  profitable   and  74.28%  said  that  they were  interested  to  develop  business  in  producing   fish  skin  chips.  All  the participants   (100%)   of  the  second   program   said  that   the  program   was profitable  and  they  were  interested  to  develop   business   in producing   fish skin  chips.  Thus,  the  program   succeeded   in  broadening   the  participants' perspectives  and  skills  on how  to make  use  of   waste,  turning  it into fish skin  chips  and  to  motivate  the  participants   to  develop   business  using  the knowledge  and skills already obtained.Key words:fish skin waste.fish skin drips